Hubungan Tingkat Depresi dan Insomnia dengan Kualitas Hidup pada Pasien yang Menderita Penyakit Kronis - Seppritah Suhenni, Erin; Mardiana, Nova; Faizal, Kgs. M. (Pustaka Galeri Mandiri, 2026)
Based on data from the Sejiran Setason Regional Hospital's Medical Record, 38 patients with chronic illnesses were found to have depression and 22 with insomnia in 2022. In 2023, 37 patients experienced depression and 21 with insomnia. The purpose of this study was to determine the relationship between levels of depression and insomnia and quality of life in patients with chronic illnesses in the Internal Medicine Clinic of Sejiran Setason Regional Hospital in 2025. The study used a quantitative cross-sectional approach, with a sample of 100 individuals. Univariate and bivariate data analysis was performed using the chi-square test. The results of the study showed that there was a significant relationship between the level of depression and the quality of life in patients suffering from chronic diseases, as evidenced by the Asymp.Sig value of 0.000 <0.05 and the POR value of 170.033, which means that patients who experience mild depression have a tendency 170.033 times greater to have a fairly good quality of life compared to patients who experience moderate depression. Furthermore, there was a significant relationship between insomnia and quality of life in patients with chronic illnesses, as evidenced by an Asymp.Sig value of 0.008 < 0.05 and POR of 0.103, indicating that patients with insomnia were 0.103 times more likely to have a moderately good quality of life compared to patients without insomnia